2017
DOI: 10.1515/ats-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Access, and Preferences of Rural and Urban Households for Cooking Energy, and the Determinants in Nigeria: A Case of Ogun State

Abstract: This study identified and compared the use of cooking energy among rural and urban households in Ogun State, Nigeria using a sample of 300 households. Empirical results indicate that electricity and gas are the least sources of cooking energy in rural area (RA) while firewood and electricity are least in urban area (UA). The level of education of the respondents was a significant (P < 0.05) factor influencing the probability of using charcoal and electricity in the RA relative to firewood, while there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This implies that respondents' awareness of the health implications associated with the use of biomass energy is associated with education. This result is in line with the findings of Nwankwo et al (2018), who also found level of education among other variables that were related to awareness and knowledge of the harmful effect of use of biomass energy to health. This suggests that efforts should be made to educate the populace on the health effect of the use of biomass energy sources, considering that it is the most available form of energy in the study area.…”
Section: Health Implications Awarenesssupporting
confidence: 91%
“…This implies that respondents' awareness of the health implications associated with the use of biomass energy is associated with education. This result is in line with the findings of Nwankwo et al (2018), who also found level of education among other variables that were related to awareness and knowledge of the harmful effect of use of biomass energy to health. This suggests that efforts should be made to educate the populace on the health effect of the use of biomass energy sources, considering that it is the most available form of energy in the study area.…”
Section: Health Implications Awarenesssupporting
confidence: 91%
“…For the calculation, it was assumed that communities sell at least 70% of the charcoal in this market. This assumption was possible because rural populations normally use firewood as cooking energy and charcoal is sold in the city markets [39,40]. The provincial market of Kuito is the main market in the province where charcoal from different municipalities is sold.…”
Section: Discussionmentioning
confidence: 99%